Safety and efficacy of cardioversion of acute atrial fibrillation – the Fincv (Finnish cardioversion) study - Grönberg, Toni (fi=Turun yliopisto|en=University of Turku|, 2017)
Background: The inherent risk of thromboembolism after cardioversion of atrial fibrillation with a duration of more than 48 hours is well established. However, the potential increased risk of these complications after cardioversion of recent-onset episodes of atrial fibrillation has been more controversial. Thus, the aim of this dissertation was to evaluate the safety and efficacy of cardioversion of acute (< 48 hours) atrial fibrillation. Methods: The FinCV study is a multicenter (n=3) retrospective study of 3143 patients who underwent 7660 cardioversions for acute atrial fibrillation. Of those procedures, 5362 were performed without, and 2298 with, anticoagulation protection. Results: The success rate of electrical cardioversions was 94.2%. After successful procedures, atrial fibrillation recurred in 17.3% of cases within 30 days. The rate of thromboembolic events (mainly ischemic strokes) was 0.7% in non-anticoagulated patients after successful cardioversion of acute atrial fibrillation. Significant independent predictors of these complications were old age, female sex, heart failure and diabetes, along with a cardioversion delay of 12 hours or longer. The risk of thromboembolism was as high as 9.8% in patients with both heart failure and diabetes. The incidence of thromboembolic complications also increased significantly from 0.4% in nonanticoagulated patients with CHA2DS2VASc score of ≤ 1 to 2.3% in those with a score of ≥ 5. Overall, the incidence of thromboembolism was significantly lower after cardioversions performed during anticoagulation (0.1% vs. 0.7%). Altogether, 0.9% of electrical cardioversions resulted in bradyarrhythmia, and 44.4% of those patients underwent pacemaker implantation later. Conclusions: The cardioversion of acute atrial fibrillation does not increase the risk of thromboembolism in anticoagulated patients. However, this risk is unacceptably high in non-anticoagulated patients with conventional risk factors for stroke. High CHA2DS2VASc score and a delay to cardioversion of 12 hours or longer are significant predictors of thromboembolism. Overall, electrical cardioversion is an effective procedure and immediate arrhythmic complications are rare after these procedures.

Akuutin eteisvärinän kardioversion turvallisuus ja teho – Fincv-tutkimus Tausta: Yli 2 vuorokautta kestäneen eteisvärinän kardioversioon liittyvä kohonnut aivohalvauksen riski on hyvin tiedossa. Sen sijaan, akuutin eteisvärinän kääntöön liittyvä aivohalvauksen riski on aikaisemmin ollut kiistanalaisempi. Tästä syystä väitöskirjatutkimuksen tarkoituksena oli selvittää akuutin (kesto alle 48 tuntia) eteisvärinän rytminsiirron turvallisuus ja teho. Menetelmät: FinCV-tutkimuksen aineisto on kerätty retrospektiivisesti kolmesta tutkimuskeskuksesta. Se sisältää tiedot 3143 potilaalle tehdystä 7660:stä akuutin eteisvärinän kardioversiosta. Näistä 2298 tehtiin antikoagulaatiohoidon aikana ja 5362 ilman vastaavaa hoitoa. Tulokset: Sähköisistä kardioversioista 94,2 % onnistui, mutta 17,3 %:lla potilaista eteisvärinä uusiutui 30 päivän seurannassa. Antikoaguloimattomilla potilailla 0,7 % onnistuneista kardioversioista johti tromboemboliseen komplikaatioon (pääosa aivoinfarkteja). Näiden komplikaatioiden itsenäisiä riskitekijöitä olivat korkea ikä, naissukupuoli, diabetes ja sydämen vajaatoiminta, yhdessä akuutin eteisvärinän käännön viivästymiseen yli 12 tuntiin kohtauksen alusta. Kardioversioon liittyvä tromboembolian riski oli erityisen suuri samanaikaisesti diabetesta ja sydämen vajaatoimintaa sairastavilla potilailla – 9,8 prosenttia. Tromboembolisten komplikaatioiden ilmaantuvuus antikoaguloimattomilla potilailla oli 2,3 prosenttia CHA2DS2VAScriskipisteiden ollessa yli neljä, kun taas potilailla, joilla riskipisteitä oli vähemmän kuin kaksi, riski oli ainoastaan 0,4 prosenttia. Antikoaguloiduilla potilailla tromboembolisten komplikaation esiintyvyys kardioversion jälkeen oli selvästi vähäisempää verrattuna antikoaguloimattomiin potilaisiin (0,1 % vs. 0,7 %). Sähköisistä kardioversioista 0,9 % johti välittömästi käännön jälkeen ilmenevään bradyarytmiaan ja 44,4 %:lle näistä potilaista asennettiin myöhemmin tahdistin. Päätelmät: Akuutin eteisvärinän rytminsiirtoon liittyy huomattava tromboembolisten komplikaatioiden vaara tietyillä potilasryhmillä. Korkea CHA2DS2VASc -pistemäärä ja rytminsiirron viivästyminen yli 12 tuntiin oireiden alusta lisäävät selvästi tätä riskiä. Antikoagulaatiohoidon aikana tehty kardioversio ei näyttäisi kuitenkaan lisäävän tromboembolian vaaraa. Sähköinen kardioversio on tehokas toimenpide ja käännön yhteydessä ilmenevät arytmiset komplikaatiot ovat harvinaisia ja hyvänlaatuisia.